2012
DOI: 10.5620/eht.2012.27.e2012007
|View full text |Cite
|
Sign up to set email alerts
|

Practical Use and Risk of Modafinil, a Novel Waking Drug

Abstract: ObjectivesModafinil is a waking drug prescribed to narcolepsy patients, but its usage among healthy individuals is increasing to enhance their alertness or to mitigate fatigue. This study was conducted to investigate practical use and toxic effects on neuro-immune interaction of modafinil.MethodsThis study reviewed the significance of psychoactive drugs, and discussed the benefits and risks of the application of modafinil, which seems to be ideal as an anti-psychotic or anti-fatigue agent.ResultsModafinil is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 60 publications
(92 reference statements)
1
40
0
Order By: Relevance
“…For conciseness, we did not compare the effect of modafinil with other central nervous system stimulants, such as methylphenidate and amphetamines. A descriptive review by Kim discusses the neural mechanisms and cognitive effects of amphetamine and caffeine and compares it to modafinil (Kim, 2012). Similar effectiveness was found.…”
Section: Discussionsupporting
confidence: 67%
“…For conciseness, we did not compare the effect of modafinil with other central nervous system stimulants, such as methylphenidate and amphetamines. A descriptive review by Kim discusses the neural mechanisms and cognitive effects of amphetamine and caffeine and compares it to modafinil (Kim, 2012). Similar effectiveness was found.…”
Section: Discussionsupporting
confidence: 67%
“…Modafinil was first approved by the US Food and Drug Administration (FDA) in 1998 and marketed as the racemic mixture of R- and S-enantiomers (2) and later as a formulation containing only the R-enantiomer, which is pharmacokinetically distinct from the S-enantiomer in humans (3) as described later (4). It has been viewed throughout its history (57) as a “novel” wake-promoting therapeutic, and apparently is still viewed in the same manner to this day (8). The fact that this mainstream therapeutic agent is still thought of as novel presumably stems from some unique pharmacological and clinically relevant properties of modafinil relative to other wake-promoting agents.…”
Section: Introductionmentioning
confidence: 99%
“…First, it has been reported that modafinil blocks dopamine transporter in animals and human brain resulted in inhibition of dopamine reuptake 17 . Inhibition of dopamine reuptake increases the extracellular levels of dopamine in the brain leading to disrupting wake-promoting actions in knock-out mice 17 . Blocking the dopamine reuptake may increase dopamine in the nucleus accumbens and can be connected to the drug abuse.…”
Section: Modafinil Tolerancementioning
confidence: 99%